Jackfruit Seeds Starch-Based Coagulant for Synthetic Textile Wastewater Remediation - Yunus, Zalilah Murni; Azaha, Nur Aina Natasha (Enhanced Knowledge in Sciences and Technology, 2021)
The chemical-based coagulant are commonly used in wastewater treatment due to its effectiveness. However, their lack of biodegradability and health hazard of the monomer residues are the main concern. Thus, starches isolated from fruit wastes and plants which rich in polysaccharides were investigated as a potential alternative as natural coagulant. In this study, jackfruit seed starch (JSS) coagulant was produced by isolating starch from jackfruit seeds using alkaline pretreatment. Physicochemical properties of JSS were studied including starch yield, amylose to amylopectin ratio, functional group, surface morphology and compositional elements. In order to assess the effectiveness of JSS coagulant, a coagulation-flocculation process was performed to observe colour and turbidity removal from synthetic textile wastewater. The parameters of coagulation-flocculation conducted are pH and coagulant dosage. It was found that the optimum parameter for coagulation-flocculation process are at pH 2 and coagulant dosage of 50 mg/L. At pH 2, 95.5% of colour and 87.5% of turbidity were removed. In addition, colour removal was up to ~100% and turbidity removal was 89.1% when 50 mg/L JSS coagulant was used. The JSS flocs were filtered and analyzed to identify chemical functional group, surface morphology and compositional elements by FTIR, SEM and EDX analysis. The most abundant functional group in JSS coagulant which is –OH group played important roles in this coagulation-flocculation process. Thus, this jackfruit seed coagulant can be one of the options of natural coagulant to be used in wastewater treatment.